(3JaQjX Ydi GdQSGdI GdecfjI aj GdYGdL HGdcfjIs
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb YfO eUGOaI GdOhGA ddOGA TaGA hHYO abO hbaJ Ydi gPG GdJCdja GdZQjH GdCfehPL Gdehba GdYLjH aCdbjJg bO GYJdG ef GdJMbjb CYdG ebGe s
(3BNQgG (B:s
(3hEf cGf ef Cgd GdJWHjH jSJYf hUd Gddg Ydi SjOfG eMeO s
(3Vef eLehY , JQJjHgG (B: 8s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs